AKUNTABILITAS PENGELOLAAN DANA DESA DALAM UPAYA PEMBANGUNAN DI DESA SAJANG KECAMATAN SEMBALUN - Baiq hanita Septiani Audia; Indah Ariffianti; Baiq Desthania Prathama (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This study aims to determine the Accountability of village fund Management to improvedevelopment in Sajang Village, Sembalun District, which consists of five stages, namelyPlanning, Implementation, administration, reporting and accaountability.This type of research isa case study using a descriptive analysis approach. In this study, the techniques of datacollection use are interviews, questionnaires and documentatation. The data analysis techniqueuse in this study is a quanlitative descriptive analysis technique.The results of this study indicatethat the planning, implementation, reporting, administration and accountability system ofaccountability has applied the principle of accountability. Thia is evidenced from the results ofinterviews with documentation and questionnaires.